2021
DOI: 10.3390/catal11080905
|View full text |Cite
|
Sign up to set email alerts
|

Cold Plasma Synthesis and Testing of NiOX-Based Thin-Film Catalysts for CO2 Methanation

Abstract: An essential problem in managing CO2 and transforming it into methane as a useful fuel is the quest for adequately efficient and cheap catalysts. Another condition is imposed by the new designs of structured reactors, which require catalysts in the form of the thinnest possible films. The aim of this work was to produce Ni-based thin-film catalysts by the cold plasma deposition method (PECVD) from a volatile metal complex (Ni(CO)4) and to study their structure and catalytic properties in the CO2 methanation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…In spite of its toxicity, Ni(CO) 4 is routinely used in laboratories to prepare organometallic complexes 6 and thin films. 7 The description of the Mond process emphasizes that Ni(CO) 4 may form whenever Ni-based catalysts are reduced and exposed to CO at temperatures below 200 °C. In fact, Hadjiivanov and co-workers 8 showed that Ni(CO) 4 formed already at −188 °C when SiO 2 -supported Ni nanoparticles (about 4 nm in diameter) were exposed to 0.2 kPa of CO.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of its toxicity, Ni(CO) 4 is routinely used in laboratories to prepare organometallic complexes 6 and thin films. 7 The description of the Mond process emphasizes that Ni(CO) 4 may form whenever Ni-based catalysts are reduced and exposed to CO at temperatures below 200 °C. In fact, Hadjiivanov and co-workers 8 showed that Ni(CO) 4 formed already at −188 °C when SiO 2 -supported Ni nanoparticles (about 4 nm in diameter) were exposed to 0.2 kPa of CO.…”
mentioning
confidence: 99%
“…In spite of its toxicity, Ni(CO) 4 is routinely used in laboratories to prepare organometallic complexes 6 and thin films. 7…”
mentioning
confidence: 99%
“…Compared to other types of plasma, the CAMP has a higher electron temperature than plasma obtained by the indirect and high-frequency discharge. Due to the high temperature of the electrons, there is also a higher dissociation and ionization degree, which is reflected in a wide range of uses of this type of discharge, including wound healing 35 , surface decontamination of fruits 36 , or deposition of thin layers 37 . Our finding suggested that CAMP has a therapeutic effect on stimulating hair regrowth through Akt/β-catenin signaling, YAP/TAZ Hippo pathway, and USP47-associated β-catenin deubiquitination in hDPCs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The meshes were pre-calcined in air at 900 °C for 48 hours. The finer mesh, denoted as A, was employed in processes related to CO 2 conversion [45,48,50,51] while the looser one (B) was used in catalytic ozonation of wastewater [49]. Figure 3 provides an example of plasma-fabricated thin-film catalysts based on CoO x on the applied support.…”
Section: Thin Film Deposition By Cold Plasmamentioning
confidence: 99%